Positive electrode additive and preparation method thereof, positive electrode plate, battery and electronic equipment

By using solid electrolyte-graphene composite materials in the positive electrode sheet of the battery, the problem of insufficient wettability of the electrolyte is solved, and the battery's magnification and cycling performance are significantly improved.

CN119812336APending Publication Date: 2025-04-11ZHEJIANG ZEEKR INTELLIGENT TECH CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510001470.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the wetting properties of the electrolyte in the positive electrode sheet of the battery, resulting in limited battery magnification and cycling performance.

Method used

A solid electrolyte-graphene composite material is used as the positive electrode additive, and a composite material with excellent conductivity and pore structure adjustment ability is prepared by calcining the raw material mixture of solid electrolyte and graphene conductive agent.

Benefits of technology

The ion and electron conductivity of the positive electrode sheet is improved, the polarization effect is reduced, the wetting and liquid absorption capacity of the electrolyte are enhanced, and the battery's magnification and circulation performance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812336A_ABST
    Figure CN119812336A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode additive and a preparation method thereof, a positive electrode plate, a battery and electronic equipment. The positive electrode additive comprises a solid electrolyte-graphene composite material, and the solid electrolyte-graphene composite material is obtained by calcining a raw material mixture comprising a solid electrolyte and a graphene conductive agent. Due to the addition of the solid electrolyte-graphene composite material, on one hand, an ion-electron transmission path can be constructed, the ion and electron conductivity of the positive pole piece is improved, and the polarization of a battery cell is reduced; on the other hand, the constructed composite material can adjust the pore structure of the positive pole piece and improve the capillary force of the electrolyte, so that the liquid absorption and retention capabilities are improved, namely the transmission rate of ions is improved, and the rate and cycle performance of the battery cell are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a positive electrode additive and a preparation method thereof, a positive electrode plate, a battery and an electronic device. Background Art

[0002] As the battery industry achieves rapid growth, improving the rate and cycle performance of batteries has always been a research hotspot. At present, improving the fast charging capability of battery cells generally focuses on the optimization of materials and formulation systems on the negative electrode, but as the size required for rate performance increases, the ionic and electronic conductivity of the positive electrode has gradually become a bottleneck restricting the fast charging capability.

[0003] The electrolyte plays a key role in improving the rate performance of the battery, but in the existing methods, the wetting effect of the electrolyte is not enough to meet the requirements of fast charging (such as 6C) or higher energy density systems. Therefore, in order to improve the wettability of the electrolyte, some studies have improved the wettability of the electrolyte in the electrode by changing the formula of the electrolyte and vacuumizing the battery cell, such as adding surfactants, adjusting the proportion of solvents, etc. In addition, there are some studies that improve the wettability of the electrolyte in the main material by changing the preparation process of the positive electrode main material, such as changing the particle size. However, these methods usually bring about other side effects, such as the risk of poor storage caused by adding other additives to the electrolyte, and the poor dispersion of the positive electrode slurry process caused by reducing the positive electrode particle size, thereby affecting the rate and cycle performance of the battery cell.

[0004] Therefore, how to improve the wettability of the electrolyte in the electrode and thus improve the rate and cycle performance of the battery is an urgent problem to be solved. Summary of the invention

[0005] The present application provides a positive electrode additive and a preparation method thereof, a positive electrode plate, a battery and an electronic device, which are used to improve the wettability of the electrolyte in the plate, reduce the polarization effect, and thus improve the rate and cycle performance of the battery.

[0006] In a first aspect, the present application provides a positive electrode additive, comprising: a solid electrolyte-graphene composite material, wherein the solid electrolyte-graphene composite material is obtained by calcining a raw material mixture including a solid electrolyte and a graphene conductive agent.

[0007] The positive electrode additive as described above, wherein the raw material mixture further comprises carbon nanotubes and / or conductive carbon black.

[0008] The positive electrode additive as described above, wherein the mass ratio of the solid electrolyte to the graphene in the solid electrolyte-graphene composite material is 1:1 to 1:5.

[0009] The positive electrode additive as described above, wherein the D50 particle size of the solid electrolyte-graphene composite material is 0.5 μm to 3 μm.

[0010] The positive electrode additive as described above, wherein the solid electrolyte-graphene composite material contains 0.1% to 2.0% oxygen by mass.

[0011] The positive electrode additive as described above, wherein the solid electrolyte is an inorganic solid electrolyte, and the solid electrolyte is selected from at least one of lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), lithium lanthanum zirconium oxide (LLZO), and lithium lanthanum titanium oxide (LLTO).

[0012] The positive electrode additive as described above, wherein the solid electrolyte is an organic solid electrolyte, and the organic solid electrolyte is selected from at least one of polyethylene oxide (PEO), polyacrylonitrile (PAN), polyamide (PA), and polyurethane (PU).

[0013] The positive electrode additive as described above, wherein the solid electrolyte is an organic-inorganic composite solid electrolyte, and the organic-inorganic composite solid electrolyte is selected from at least one of a PEO-LATP composite material, a PAN-LLZO composite material, a composite material of polyurethane and LLTO, and a composite material of polyethylene oxide and ceramic material.

[0014] The positive electrode additive as described above, wherein the graphene conductive agent has a specific surface area of ​​258m 2 / g~893m 2 / g.

[0015] The positive electrode additive as described above, wherein the D 50 The particle size is 0.2μm~0.6μm.

[0016] In a second aspect, the present application provides a method for preparing a positive electrode additive as described in any one of the first aspects, the method comprising:

[0017] The graphene conductive agent and the solid electrolyte are calcined to obtain a solid electrolyte-graphene composite material as the positive electrode additive.

[0018] In some possible implementations, if the solid electrolyte is an inorganic solid electrolyte, the calcination temperature is 700°C to 900°C, the time is 8 to 12 hours, and the atmosphere is an inert gas; if the solid electrolyte contains an organic solid electrolyte, the calcination temperature is 120°C to 140°C, the time is 8 to 12 hours, and the atmosphere is an inert gas.

[0019] In some possible implementations, the method further includes:

[0020] Prepare graphene conductive agent by liquid phase exfoliation method or redox method;

[0021] The liquid phase exfoliation method comprises the following steps: mechanical exfoliation of the expanded graphite raw material in an aqueous phase system for a treatment time of 2 hours to 4 hours, followed by flash drying for 1 hour to 2 hours;

[0022] The steps of the oxidation-reduction method include: using graphite, concentrated sulfuric acid and potassium permanganate as raw materials, preparing graphite into graphene oxide by an oxidation method, and then obtaining graphene by thermal reduction of the graphene oxide; wherein the thermal reduction temperature is set to 700° C. to 1200° C., the time is 3 h to 8 h, and the atmosphere is an inert gas.

[0023] In a third aspect, the present application further provides a positive electrode sheet, comprising: a positive electrode current collector, and a positive electrode coating located on one side surface of the positive electrode current collector, wherein the positive electrode coating comprises an active layer and a conductive layer;

[0024] The active layer comprises a main material, such as the positive electrode additive as described in any one of the first aspects, and a binder.

[0025] The positive electrode plate as described above, wherein the additive accounts for 1% to 2% by mass in the positive electrode plate.

[0026] In a fourth aspect, the present application further provides a battery, comprising the positive electrode sheet described in any one of the third aspects.

[0027] In a fifth aspect, the present application also provides an electronic device, comprising the battery described in the fourth aspect.

[0028] The positive electrode additive of the present application includes a solid electrolyte-graphene composite material, which is obtained by calcining a raw material mixture including a solid electrolyte and a graphene conductive agent. The addition of the solid electrolyte-graphene composite material can, on the one hand, construct an ion-electron transmission pathway, improve the ion and electron conductivity of the positive electrode plate, and reduce the polarization of the battery cell; on the other hand, the constructed composite material can adjust the pore structure of the positive electrode plate, improve the capillary force of the electrolyte, thereby improving the liquid absorption and liquid retention capacity, that is, improving the ion transmission rate, thereby improving the rate and cycle performance of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A schematic diagram of the positive electrode provided in this application;

[0030] Figure 2 Schematic diagram of SEM characterization of graphene powder prepared by physical and chemical methods;

[0031] Figure 3Schematic diagram of SEM characterization of graphene-solid electrolyte composite materials prepared by physical and chemical methods and applied in positive electrode sheets. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below in combination with the embodiments of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0033] The rate refers to the ability of a battery to output a high current in a short period of time. Improving the rate and cycle performance of a battery has always been a hot research topic. If the polarization effect is significant, the reaction rate in the battery will be limited, resulting in reduced output capacity. Therefore, reducing the polarization effect is the key to improving the rate, and increasing the ion-electron conductivity and reducing the polarization effect of the battery during the charge and discharge process is one of the main measures currently taken.

[0034] The rate can be increased in two ways:

[0035] The first point is to build a reasonable conductive and ion-conducting pathway. At present, improving the fast-charging capacity of battery cells generally focuses on the optimization of materials and formula systems on the negative electrode. However, as the size required for rate performance increases, the ionic and electronic conductivity of the positive electrode has gradually become a bottleneck restricting the fast-charging capacity. Adding solid electrolytes to the positive electrode is a key measure to improve the ionic conductivity of the positive electrode, such as oxide solid electrolytes. However, its small particle size also leads to the disadvantage of easy agglomeration at the application end. At the same time, poor contact with the main material further limits its application at the battery end.

[0036] The second point is to increase the wetting speed of the electrolyte. The existing solutions to improve the wettability of the electrolyte are mainly to change the formula of the electrolyte and vacuum the battery cell, such as adding surfactants, adjusting the proportion of solvents, etc. to improve the wettability of the electrolyte in the electrode. In addition, there are some studies that improve the wettability of the electrolyte in the main material by changing the preparation process of the positive electrode main material, such as changing the particle size. These methods usually bring about other side effects, such as the risk of poor storage caused by adding other additives to the electrolyte, and poor dispersion of the positive electrode slurry process caused by reducing the size of the positive electrode particles.

[0037] This application is designed based on the principle of electrolyte infiltration. The electrolyte infiltration principle is: the electrolyte infiltration process in the electrode is a spontaneous liquid adsorption process driven by capillary force. Ignoring the influence of inertia and gravity, the amount of electrolyte adsorption is affected by factors such as electrolyte surface tension, viscosity, electrode pore structure, main material surface properties, ambient temperature and humidity, and internal and external pressure differences. The calculation formula for capillary force is: h = 2σcosθ / ΔρgR, where h represents the height of the liquid rise (i.e., the electrolyte infiltration depth), σ represents the surface tension of the electrolyte, which determines the viscosity of the electrolyte, θ represents the contact angle between the electrolyte and the electrode surface, Δρ represents the density difference between the electrolyte and the gas, g represents the gravitational acceleration, and R represents the radius of the pore. From the above formula, it can be determined that the electrolyte infiltration depth is inversely proportional to the pore radius R. The smaller the pore radius, the more conducive to the infiltration of the electrolyte. The deeper the electrolyte penetration depth, the faster the penetration speed at the same penetration time.

[0038] It can be seen from the above formula that in order to improve the wetting effect of the electrolyte, it is effective to appropriately reduce the electrode aperture, increase the surface tension of the electrolyte, and reduce the viscosity of the electrolyte.

[0039] In view of the above problems and the principle of electrolyte infiltration, this application prepares positive electrode additives by sintering graphene and solid electrolyte. First, by taking advantage of the characteristics of small pores of graphene, adding graphene can regulate the pore structure of the positive electrode plate, and in the process of electrolyte infiltration of the plate, increase the migration rate of the electrolyte in the pores, thereby improving the infiltration effect of the electrolyte. Secondly, preparing composite materials by sintering also helps the dispersion effect of solid electrolyte and graphene, plays a role in inhibiting their agglomeration, and further improves ionic conductivity.

[0040] Based on this, the first aspect of the present application provides a positive electrode additive, including: a solid electrolyte-graphene composite material, wherein the solid electrolyte-graphene composite material is obtained by calcining a raw material mixture including a solid electrolyte and a graphene conductive agent.

[0041] The addition of solid electrolyte-graphene composite materials constructs ion-electron transmission pathways, increases the contact area for ion and electron transmission, improves the ion and electron conductivity of the positive electrode, and reduces the polarization of the battery cell. The composite material is prepared by sintering, which mainly contributes to the dispersion effect of the solid electrolyte through the Van der Waals force-related effect and plays a role in inhibiting the agglomeration of the solid electrolyte.

[0042] Because graphene is layered and its particle size is controllable, the pore structure of the composite material can also be adjusted. Therefore, the solid electrolyte-graphene composite material can improve the pore structure of the electrode, increase the capillary force of the electrolyte, and thus improve the ability to absorb and retain liquid, that is, to increase the transmission rate of ions.

[0043] Taking advantage of the high specific surface area of ​​graphene conductive agent, its affinity with the electrolyte is increased. At the same time, the roughness of the surface of the main material particles coated reduces the obstruction of the electrolyte infiltration process and improves the wetting effect of the electrolyte in the positive electrode.

[0044] In some embodiments, the introduction of carbon nanotubes and / or conductive carbon black helps to adjust the pore structure of the composite material, forming a more optimized capillary structure, thereby improving the wettability and ion transmission capacity of the electrolyte. Therefore, the raw material mixture also includes carbon nanotubes and / or conductive carbon black, which are calcined and compounded together with the solid electrolyte and graphene conductive agent. In addition, carbon nanotubes and / or conductive carbon black can fill the gap between the solid electrolyte and graphene, increase the contact area between the electrode and the electrolyte, reduce the interface impedance, and further improve the battery performance.

[0045] In some embodiments, according to the principle of capillary phenomenon, materials with smaller particle sizes help improve the wetting ability of the electrolyte, making it easier for it to penetrate into the electrode and reducing the wetting resistance of the electrolyte. In addition, smaller particle sizes can provide a larger specific surface area, thereby enhancing the contact and transmission efficiency of ions and improving the charge and discharge performance of the battery. Therefore, the D 50 The particle size is 0.5 μm to 3 μm. For example, the D 50 The particle size may be 0.5 μm, 0.7 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 2.7 μm, 3 μm or a range consisting of any two of the above values.

[0046] In some embodiments, in the solid electrolyte-graphene composite material, a higher proportion of graphene helps to significantly improve the electronic conductivity of the composite material, thereby improving the overall performance of the battery, especially at high rate discharge; in addition, the ion channels in the composite material are also formed by the graphene pores. Therefore, the mass ratio of the solid electrolyte to the graphene is 1:1 to 1:5. Exemplarily, the D of the solid electrolyte-graphene composite material 50 The particle size can be 1:1, 1:2, 1:3, 1:4, 1:5 or a range consisting of any two ratios thereof.

[0047] In some embodiments, the oxygen content in the solid electrolyte-graphene composite material is 0.1% to 2.0%. The specific oxygen content is related to the preparation of the graphene conductive agent. When the graphene conductive agent is prepared by the redox method, the oxygen content in the graphene conductive agent can be controlled, and then the oxygen content in the solid electrolyte-graphene composite material can be controlled. Chemically prepared graphene has certain oxygen-containing functional groups, mainly hydroxyl and epoxy. The conductive agent is applied to the positive electrode plate, and the oxygen-containing polar functional groups therein can improve the affinity with the electrolyte, thereby improving the wettability of the electrolyte. In addition, the oxygen-containing functional groups in the graphene and the solid electrolyte carrying the oxygen element undergo hydrogen bonding and van der Waals forces, which contribute to the dispersion effect of the solid electrolyte and inhibit its agglomeration. For the graphene conductive agent prepared by the physical stripping method, it generally does not contain oxygen-containing functional groups, and its oxygen element comes from the solid electrolyte carrying the oxygen element.

[0048] In some embodiments, the solid electrolyte is an inorganic solid electrolyte, and the solid electrolyte is selected from at least one of lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), lithium lanthanum zirconium oxide (LLZO), and lithium lanthanum titanium oxide (LLTO). The inorganic solid electrolyte has a high ionic conductivity, which helps to improve the energy density and power density of the battery. In addition, it has excellent thermal stability and can maintain stable performance.

[0049] In some embodiments, the solid electrolyte is an organic solid electrolyte, and the organic solid electrolyte is selected from at least one of polyethylene oxide (PEO), polyacrylonitrile (PAN), polyamide (PA), and polyurethane (PU). The organic solid electrolyte can improve the migration channel of ions. In addition, compared with inorganic solid electrolytes, organic materials are more flexible, can adapt to different battery shapes and sizes, and reduce mechanical stress.

[0050] In some embodiments, the solid electrolyte is an organic-inorganic composite solid electrolyte, and the organic-inorganic composite solid electrolyte is selected from at least one of a PEO-LATP composite material, a PAN-LLZO composite material, a composite material of polyurethane and LLTO, and a composite material of polyethylene oxide and ceramic material. Inorganic components generally provide high ionic conductivity, while organic components can improve the migration channel of ions, and the synergistic effect between organic and inorganic components can significantly improve ionic conductivity.

[0051] In some embodiments, the specific surface area of ​​the graphene conductive agent is 258 m 2 / g~893m 2 / g. Exemplarily, the specific surface area of ​​the graphene conductive agent can be 258m 2 / g, 316m 2 / g, 513m 2 / g, 649m 2 / g, 721m 2 / g、746m 2 / g、893m 2 / g, 603m 2 / g, 577m 2 / g or a range consisting of any two of the above values.

[0052] In some embodiments, the solid electrolyte has a D 50 The particle size is 0.2 μm to 0.6 μm. For example, the D 50 The particle size may be 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm or a range consisting of any two of the above values.

[0053] The second aspect of the present application provides a method for preparing the positive electrode active material of the first aspect, comprising:

[0054] The graphene conductive agent and the solid electrolyte are calcined to obtain a solid electrolyte-graphene composite material as a positive electrode additive. The graphene conductive agent can be purchased or prepared.

[0055] Calcination can promote the good combination of graphene and solid electrolyte, improve the compatibility between the two, and enhance the overall structural stability of the composite material. Calcination can promote solid-state reactions and form a new phase between graphene and solid electrolyte. In addition, through calcination, the structure of graphene can be further optimized, defects can be reduced, and its conductive properties can be improved, so that the composite material performs better in battery applications.

[0056] In some embodiments, if the solid electrolyte is an inorganic solid electrolyte, the calcination temperature range is 700°C to 900°C, the time is 8h to 12h, and the atmosphere is an inert gas. In an inert gas atmosphere, temperatures below 900°C will not deteriorate graphene, and the two are combined as much as possible by calcination. Exemplarily, the calcination temperature can be 700°C, 750°C, 800°C, 850°C, 900°C or a range consisting of any two of the above values. The calcination time can be 8h, 9h, 10h, 11h, 12h or a range consisting of any two of the above values. The inert gas can be N2 or Ar.

[0057] In some embodiments, if the solid electrolyte includes an organic solid electrolyte or an inorganic-organic composite solid electrolyte, the calcination temperature needs to be below its decomposition temperature, the temperature range is 120°C to 140°C, the time is 8h to 12h, and the atmosphere is an inert gas. In an inert gas atmosphere, the two are combined as much as possible by calcination, while ensuring that the organic solid electrolyte does not decompose. For example, the calcination temperature can be 120°C, 125°C, 130°C, 140°C or a range consisting of any two of the above values. The calcination time can be 8h, 9h, 10h, 11h, 12h. The inert gas can be N2 or Ar.

[0058] In some embodiments, the graphene conductive agent is prepared by a liquid phase exfoliation method; wherein the steps of the liquid phase exfoliation method include: mechanical exfoliation of the expanded graphite raw material in an aqueous system for 2 hours to 4 hours, and then flash drying for 1 hour to 2 hours. Exemplarily, the processing time can be 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, and the flash drying time can be 1 hour, 1.2 hours, 1.5 hours, 1.8 hours, 2 hours, or a range consisting of any two of the above values.

[0059] In some embodiments, a graphene conductive agent is prepared by a redox method; wherein the steps of the redox method include: using graphite, concentrated sulfuric acid, and potassium permanganate as raw materials, preparing graphite into graphene oxide by an oxidation method, and then obtaining graphene by thermal reduction of the graphene oxide; wherein the thermal reduction temperature is set to 700°C to 1200°C, the time is 3h to 8h, and the atmosphere is a N2 environment. Exemplarily, the thermal reduction temperature setting can be 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, and the thermal reduction time can be 3h, 4h, 5h, 6h, 7h, 8h or a range consisting of any two of the above values. In this process, the reactant ratio can be changed to change the oxygen content in the graphene, and the oxidation time can be extended to increase the degree of oxidation, thereby increasing the oxygen content, and the desired oxygen content can also be achieved by adjusting the temperature of the oxidation reaction.

[0060] The third aspect of the present application provides a positive electrode sheet, Figure 1 A schematic diagram of the positive electrode provided in this application, such as Figure 1 As shown, the positive electrode sheet includes: a positive electrode current collector, and a positive electrode coating located on one side surface of the positive electrode current collector, and the positive electrode coating includes an active layer and a conductive layer;

[0061] The active layer comprises a main material, such as the positive electrode additive of any one of the first aspects, and a binder.

[0062] The use of solid electrolyte-graphene composite materials in the positive electrode can construct an effective ion transmission channel, increase the migration speed of ions, and also adjust the pore structure of the electrode, enhance the capillary action of the electrolyte, and improve the wettability of the electrolyte, thereby improving the ion transmission efficiency.

[0063] In some embodiments, the additive accounts for 1% to 2% by mass in the positive electrode sheet, and is exemplarily 1%, 1.2%, 1.5%, 1.8%, 2% or a range consisting of any two of the above values.

[0064] In some embodiments, the main material of the positive electrode sheet is at least one of lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium cobalt oxide, and lithium manganese iron phosphate.

[0065] In some embodiments, the binder is at least one polyvinylidene fluoride (PVDF) prepared by an emulsion method or a suspension method. In a specific implementation, the mass percentage of PVDF added to the positive electrode sheet is 1.5% to 3%. Exemplarily, 1.5%, 1.8%, 2.0%, 2.5%, 3% or a range consisting of any two of the above values.

[0066] In some embodiments, the conductive layer includes a host material, a binder, and a matrix.

[0067] The main material of the conductive layer is one or more of conductive carbon black, carbon nanotubes, and graphene.

[0068] The conductive layer binder is at least one of sodium carboxymethyl cellulose and polyacrylic acid.

[0069] In some embodiments, the thickness of the conductive layer is 0.1-1.5 μm. For example, the thickness of the conductive layer is 0.1 μm, 0.3 μm, 0.5 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.5 μm, or a range consisting of any two of the above values.

[0070] In some embodiments, the conductive layer substrate is aluminum foil with a thickness of 9 to 15 μm. Exemplarily, the thickness of the aluminum foil is 9 μm, 10 μm, 12 μm, 13 μm, 15 μm, or a range consisting of any two of the above values.

[0071] In some embodiments, the compaction density of the lithium iron phosphate positive electrode sheet is 2.56 g / cc to 2.60 g / cc. Exemplarily, the compaction density of the lithium iron phosphate positive electrode sheet is 2.56 g / cc, 2.57 g / cc, 2.58 g / cc, 2.59 g / cc, 2.60 g / cc or a range consisting of any two of the above values.

[0072] In some embodiments, the compaction density of the nickel cobalt manganese oxide lithium positive electrode sheet is 3.30 g / cc to 3.60 g / cc. Exemplarily, the compaction density of the nickel cobalt manganese oxide lithium positive electrode sheet is 3.30 g / cc, 3.40 g / cc, 3.50 g / cc, 3.60 g / cc or a range consisting of any two of the above values.

[0073] The fourth aspect of the present application provides a battery, including a positive electrode sheet, a negative electrode sheet, and a separator as described in any one of the third aspects, which are arranged between the positive electrode sheet and the negative electrode sheet; an electrolyte is filled into the positive electrode sheet, the negative electrode sheet, and the separator of the battery cell. The composite material increases the transmission contact area of ​​ions and electrons by constructing an ion-electron transmission pathway, significantly improves the conductivity of the positive electrode sheet, and reduces the polarization effect. The pore structure of the composite material is adjustable, which can optimize the pore size distribution of the electrode sheet, enhance the capillary force of the electrolyte, help improve the electrolyte's ability to absorb and retain liquid, and promote the rapid transmission of ions. The high specific surface area of ​​graphene and the advantages of its surface roughness increase the affinity with the electrolyte, reduce obstacles in the wetting process, improve the wetting effect of the electrolyte in the positive electrode sheet, and further improve the accessibility of ions. Through the above effects, the battery rate performance is increased.

[0074] The fifth aspect of the present application provides an electronic device, including a battery as in the fourth aspect, which can increase the charging efficiency of the device and improve the user experience.

[0075] The present application is further described below through specific embodiments.

[0076] Embodiment 1

[0077] Using expanded graphite as raw material, graphene powder was prepared by liquid phase mechanical exfoliation method, and its specific surface area was 316m 2 The graphene powder and LATP were calcined in a mass ratio of 1:1 to prepare a LATP-graphene composite material. The composite material was added to NMP solvent to prepare a solution with a solid content of 6.8%, and sand-milled in a sand mill at 2000 rpm for 4 hours to obtain a particle size of D 50 The LATP-graphene composite slurry is 0.5μm and the graphene thickness is 10 layers. Lithium iron phosphate, binder PVDF prepared by emulsion method, conductive carbon black, carbon nanotubes and LATP graphene composite materials are homogenized in a mass ratio of 96%: 2%: 1%: 0.5%: 0.5% to prepare lithium iron phosphate positive electrode slurry. The positive electrode slurry is coated on a carbon-coated aluminum foil, and then rolled to obtain a lithium iron phosphate positive electrode sheet, and the rolling compaction density test is 2.58g / cc. The average pore size of the positive electrode sheet measured by mercury pressure method is 43.29nm. The electrolyte absorption of the positive electrode sheet tested within 3 minutes is 0.28g / cm 2The positive electrode sheet was paired with a graphite negative electrode to assemble a lithium iron phosphate lithium-ion battery, which was cycled for 500 cycles under 4C / 1C charge and discharge conditions, with a capacity retention rate of 90.1%.

[0078] Embodiment 2:

[0079] Using expanded graphite as raw material, graphene powder was prepared by liquid phase mechanical exfoliation method, and its specific surface area was tested to be 258m 2 The graphene powder and LATP were calcined at a mass ratio of 5:1 to prepare a LATP-graphene composite material. The composite material was added to NMP solvent to prepare a solution with a solid content of 8%, and sand-milled at 2000 rpm for 2 hours to obtain a particle size of D 50 The LATP-graphene composite slurry is 3.0μm and the graphene thickness is 20 layers. The lithium iron phosphate, the binder PVDF prepared by the suspension method and the LATP graphene composite material are homogenized in a mass ratio of 96%:2%:2% to prepare a lithium iron phosphate positive electrode slurry. The positive electrode slurry is coated on a carbon-coated aluminum foil, and then rolled to obtain a lithium iron phosphate positive electrode sheet. The rolling compaction density test is 2.58g / cc. The average pore size of the positive electrode sheet measured by the mercury pressure method is 45.40nm. The electrolyte absorption of the positive electrode sheet tested within 3 minutes is 0.29g / cm 2 The positive electrode sheet was paired with a graphite negative electrode to assemble a lithium iron phosphate lithium-ion battery, which was cycled for 500 cycles under 4C / 1C charge and discharge conditions, with a capacity retention rate of 90.5%.

[0080] Embodiment 3:

[0081] The graphene powder was prepared by redox chemistry, and its specific surface area was 893m 2 / g, oxygen content is 1%. The graphene powder and LATP are calcined in a mass ratio of 2:1 to prepare a LATP-graphene composite material. The graphene powder is added to NMP solvent to prepare a solution with a solid content of 3%, and the solution is averaged 10 times in a high-pressure homogenizer to obtain a particle size D 50 The LATP-graphene composite slurry is 0.5μm and the graphene thickness is 3 layers. Lithium iron phosphate, binder PVDF prepared by suspension method, carbon nanotubes and LATP graphene composite materials are homogenized in a mass ratio of 96%: 2%: 0.5%: 1.5% to prepare lithium iron phosphate positive electrode slurry. The positive electrode slurry is coated on a carbon-coated aluminum foil, and then rolled to obtain a lithium iron phosphate positive electrode sheet, and the rolling compaction density test is 2.59g / cc. The average pore size of the positive electrode sheet measured by mercury pressure method is 57.66nm. The electrolyte absorption of the positive electrode sheet tested within 3 minutes is 0.41g / cm 2The positive electrode sheet was paired with a graphite negative electrode to assemble a lithium iron phosphate lithium-ion battery, which was cycled for 500 cycles under 4C / 1C charge and discharge conditions, with a capacity retention rate of 91.3%.

[0082] Embodiment 4:

[0083] The graphene powder was prepared by redox chemistry, and its specific surface area was 746m 2 / g, oxygen content is 0.7%. The graphene powder and LATP were composite calcined at a mass ratio of 2.5:1 to prepare a LATP-graphene composite material. The composite material was added to NMP solvent to prepare a solution with a solid content of 5.1%, and averaged 10 times in a high-pressure homogenizer to obtain a particle size D 50 The LATP-graphene composite slurry is 1.2μm and the graphene thickness is 5 layers. Lithium iron phosphate, binder PVDF prepared by suspension method, conductive carbon black, carbon nanotubes and graphene-LATP composite material are homogenized in a mass ratio of 96%: 2%: 1%: 0.3%: 0.7% to prepare lithium iron phosphate positive electrode slurry. The positive electrode slurry is coated on a carbon-coated aluminum foil, and then rolled to obtain a lithium iron phosphate positive electrode sheet. The rolling compaction density test is 2.58g / cc. The average pore size of the positive electrode sheet measured by mercury pressure method is 53.93nm. The electrolyte absorption of the positive electrode sheet tested within 3 minutes is 0.38g / cm 2 The positive electrode sheet was paired with a graphite negative electrode to assemble a lithium iron phosphate lithium-ion battery, which was cycled for 500 cycles under 4C / 1C charge and discharge conditions, with a capacity retention rate of 91.1%.

[0084] Embodiment 5:

[0085] The graphene powder was prepared by redox chemistry, and its specific surface area was 513m 2 / g, oxygen content is 1.5%. The graphene powder and LATP were composite calcined at a mass ratio of 2:1 to prepare a LATP-graphene composite material. The composite material was added to NMP solvent to prepare a solution with a solid content of 5.9%, and averaged 10 times in a high-pressure homogenizer to obtain a particle size D 50The LATP-graphene composite slurry is 2.0μm and the graphene thickness is 10 layers. Lithium iron phosphate, binder PVDF prepared by suspension method, conductive carbon black, carbon nanotubes and graphene-LATP composite material are homogenized in a mass ratio of 96%:2%:1%:0.7%:0.3% to prepare lithium iron phosphate positive electrode slurry. The positive electrode slurry is coated on a carbon-coated aluminum foil, and then rolled to obtain a lithium iron phosphate positive electrode sheet, and the rolling compaction density test is 2.59g / cc. The average pore size of the positive electrode sheet measured by mercury pressure method is 44.68nm. The electrolyte absorption of the positive electrode sheet tested within 3 minutes is 0.29g / cm 2 The positive electrode sheet was paired with a graphite negative electrode to assemble a lithium iron phosphate lithium-ion battery, which was cycled for 500 cycles under 4C / 1C charge and discharge conditions, with a capacity retention rate of 90.8%.

[0086] Embodiment 6:

[0087] The graphene powder was prepared by redox chemistry, and its specific surface area was 721m 2 / g, oxygen content is 2.0%. The graphene powder and LATP were composite calcined at a mass ratio of 4:1 to prepare a LATP-graphene composite material. The graphene powder was added to NMP solvent to prepare a solution with a solid content of 3.7%, and sand-milled at 2000 rpm for 3 hours to obtain a particle size D 50 The LATP-graphene composite slurry is 1.7μm and the graphene thickness is 5 layers. Lithium manganese iron phosphate, binder PVDF prepared by suspension method, conductive carbon black, carbon nanotubes and LATP-graphene composite materials are homogenized in a mass ratio of 96%: 2%: 1%: 0.5%: 0.5% to prepare lithium manganese iron phosphate positive electrode slurry. The positive electrode slurry is coated on a carbon-coated aluminum foil, and then rolled to obtain a lithium manganese iron phosphate positive electrode sheet, and the rolling compaction density test is 2.59g / cc. The average pore size of the positive electrode sheet measured by mercury pressure method is 46.31nm. The electrolyte absorption of the positive electrode sheet tested within 3 minutes is 0.31g / cm 2 The positive electrode sheet was paired with a graphite negative electrode to assemble a lithium-ion battery of lithium manganese iron phosphate. The battery was cycled for 500 cycles under 4C / 1C charge and discharge conditions, and the capacity retention rate was 91.1%.

[0088] Embodiment 7:

[0089] The graphene powder was prepared by redox chemistry, and its specific surface area was 649m 2 / g, oxygen content is 0.5%. The graphene powder and LATP are calcined at a mass ratio of 1.5:1 to prepare a LATP-graphene composite material. The composite material is added to NMP solvent to prepare a solution with a solid content of 4.5%, and sand milled at 2000 rpm for 4 hours to obtain a particle size D 50 The LATP-graphene composite slurry is 2.0μm and the graphene thickness is 7 layers. Lithium nickel cobalt manganese oxide, binder PVDF prepared by suspension method, conductive carbon black, carbon nanotubes and LATP-graphene composite materials are homogenized in a mass ratio of 96%: 2%: 1%: 0.5%: 0.5% to prepare a lithium nickel cobalt manganese oxide positive electrode slurry. The positive electrode slurry is coated on a carbon-coated aluminum foil, and then rolled to obtain a lithium nickel cobalt manganese oxide positive electrode sheet, and the rolling compaction density test is 3.30g / cc. The average pore size of the positive electrode sheet was measured by mercury pressure method to be 47.65nm. The electrolyte absorption of the positive electrode sheet in 3 minutes is 0.65g / cm 2 The positive electrode sheet was paired with a graphite negative electrode to assemble a nickel-cobalt-manganese-oxide lithium-ion battery. The battery was cycled for 500 cycles under 4C / 1C charge and discharge conditions, and the capacity retention rate was 90.3%.

[0090] Embodiment 8:

[0091] The graphene powder was prepared by redox chemistry, and its specific surface area was 522m 2 / g, oxygen content is 1.0%. The graphene powder and LATP were composite calcined at a mass ratio of 3.7:1 to prepare a LATP-graphene composite material. The composite material was added to NMP solvent to prepare a solution with a solid content of 5.7%, and sand-milled at 2000 rpm for 3 hours to obtain a particle size D 50 The LATP-graphene composite slurry is 1.2μm and the graphene thickness is 9 layers. Lithium nickel cobalt manganese oxide, binder PVDF prepared by suspension method, conductive carbon black, carbon nanotubes and LATP-graphene composite materials are homogenized in a mass ratio of 96%: 2%: 1%: 0.3%: 0.7% to prepare a lithium nickel cobalt manganese oxide positive electrode slurry. The positive electrode slurry is coated on a carbon-coated aluminum foil, and then rolled to obtain a lithium iron phosphate positive electrode sheet, and the rolling compaction density test is 3.60g / cc. The average pore size of the positive electrode sheet was measured by mercury pressure method to be 45.44nm. The electrolyte absorption of the positive electrode sheet in 3 minutes is 0.61g / cm 2 The positive electrode sheet was paired with a graphite negative electrode to assemble a nickel-cobalt-manganese-oxide lithium-ion battery. The battery was cycled for 500 cycles under 4C / 1C charge and discharge conditions, and the capacity retention rate was 89.2%.

[0092] Embodiment 9:

[0093] The graphene powder was prepared by redox chemistry, and its specific surface area was 603m 2 / g, oxygen content is 0.4%. The graphene powder and PEO are composite calcined at a mass ratio of 1:1, and the calcination temperature is 120°C to prepare a PEO-graphene composite material. The composite material is added to NMP solvent to prepare a solution with a solid content of 4.6%, and sand milled in a sand mill at 2000 rpm for 2 hours to obtain a particle size D 50 The LATP-graphene composite slurry is 1.9μm and the graphene thickness is 7 layers. Lithium iron phosphate, binder PVDF prepared by suspension method, conductive carbon black, carbon nanotubes and PEO-graphene composite materials are homogenized in a mass ratio of 96%: 2%: 1%: 0.5%: 0.5% to prepare lithium iron phosphate positive electrode slurry. The positive electrode slurry is coated on a carbon-coated aluminum foil, and then rolled to obtain a lithium iron phosphate positive electrode sheet. The rolling compaction density test is 2.61g / cc. The average pore size of the positive electrode sheet measured by mercury pressure method is 45.3nm. The electrolyte absorption of the positive electrode sheet tested within 3 minutes is 0.62g / cm 2 The positive electrode sheet was paired with a graphite negative electrode to assemble a lithium iron phosphate lithium-ion battery, which was cycled for 500 cycles under 4C / 1C charge and discharge conditions, with a capacity retention rate of 90.2%.

[0094] Embodiment 10:

[0095] The graphene powder was prepared by redox chemistry, and its specific surface area was 577m 2 / g, oxygen content is 0.9%. The graphene powder and PEO-LATP were composite calcined at a mass ratio of 1:1, and the calcination temperature was 140°C to prepare a PEO-LATP-graphene composite material. The composite material was added to NMP solvent to prepare a solution with a solid content of 5.6%, and sand-milled at 2000 rpm for 3 hours in a sand mill to obtain a particle size D 50 The PEO-LATP-graphene composite slurry is 1.3μm and the graphene thickness is 9 layers. Lithium iron phosphate, binder PVDF prepared by suspension method, conductive carbon black, carbon nanotubes and PEO-LATP-graphene composite materials are homogenized in a mass ratio of 96%:2%:1%:0.5%:0.5% to prepare lithium iron phosphate positive electrode slurry. The positive electrode slurry is coated on a carbon-coated aluminum foil, and then rolled to obtain a lithium iron phosphate positive electrode sheet, and the rolling compaction density test is 2.59g / cc. The average pore size of the positive electrode sheet measured by mercury pressure method is 44.5nm. The electrolyte absorption of the positive electrode sheet tested within 3 minutes is 0.56g / cm 2The positive electrode sheet was paired with a graphite negative electrode to assemble a lithium iron phosphate lithium-ion battery, which was cycled for 500 cycles under 4C / 1C charge and discharge conditions, with a capacity retention rate of 90.6%.

[0096] Comparative Example 1:

[0097] Lithium iron phosphate, PVDF and conductive carbon black were homogenized in a mass ratio of 96%:2%:2% to prepare lithium iron phosphate positive electrode slurry. The positive electrode slurry was coated on carbon-coated aluminum foil and then rolled to obtain a lithium iron phosphate positive electrode sheet. The rolling compaction density test was 2.57g / cc. The average pore size of the positive electrode sheet was measured by mercury pressure method to be 42.13nm. The electrolyte absorption of the positive electrode sheet within 3 minutes was tested to be 0.27g / cm 2 The positive electrode sheet was paired with a graphite negative electrode to assemble a lithium iron phosphate lithium-ion battery, which was cycled for 500 cycles under 4C / 1C charge and discharge conditions, with a capacity retention rate of 87.3%.

[0098] Comparative Example 2:

[0099] The lithium iron phosphate, PVDF, conductive carbon black and carbon nanotube slurry were homogenized in a mass ratio of 96%:2%:1.5%:0.5% to prepare a lithium iron phosphate positive electrode slurry. The positive electrode slurry was coated on a carbon-coated aluminum foil, and then rolled to obtain a lithium iron phosphate positive electrode sheet. The rolling compaction density test was 2.56g / cc. The average pore size of the positive electrode sheet was measured by mercury pressure method to be 42.56nm. The electrolyte absorption of the positive electrode sheet within 3 minutes was tested to be 0.27g / cm 2 The positive electrode sheet was paired with a graphite negative electrode to assemble a lithium iron phosphate lithium-ion battery, which was cycled for 500 cycles under 4C / 1C charge and discharge conditions, with a capacity retention rate of 88.1%.

[0100] Test example

[0101] A method for preparing a positive electrode sheet and a lithium-ion battery for improving ion and electron conductivity comprises the following steps:

[0102] 1) First, prepare graphene powder by physical liquid phase exfoliation or chemical oxidation-reduction method, and test the properties of graphene powder such as oxygen content.

[0103] 2) calcining the graphene powder and the solid electrolyte LATP to obtain a LATP-graphene composite material

[0104] 3) The graphene powder is dissolved in NMP solvent, and after sand grinding or homogenization, it is configured into graphene conductive slurry, and its sheet diameter and thickness are tested.

[0105] 4) The graphene slurry is used as a conductive agent and added to the lithium iron phosphate or lithium nickel cobalt manganese oxide positive electrode slurry, and the positive electrode sheet is obtained through coating, baking and rolling processes.

[0106] 5) Test the parameters such as the porosity and liquid absorption performance of the positive electrode plate.

[0107] 6) The positive electrode sheet, the negative electrode sheet and the separator are assembled into a bare cell through a lamination process, and the bare cell is completed after the tab welding, mylar wrapping, cover welding, shell cover welding, baking, liquid injection, formation and capacity division to complete the production of soft pack or square shell cell.

[0108] 7) Testing the cycle and rate performance of the assembled battery.

[0109] Material Testing:

[0110] 1. Specific surface area test (nitrogen low temperature adsorption method)

[0111] 1) Place ~100 mg of the sample to be tested into a sample tube.

[0112] 2) Install the sample tube into the degassing station, align the port, and tighten the screws to ensure a secure seal. Then put the heating pack on the sample tube, set the file information and degassing temperature and other parameters, turn on the vacuum pump, and start heating and vacuum degassing the sample to remove the gas adsorbed on the surface of the material.

[0113] 3) After degassing, turn off the heating power supply, wait for the sample to cool to room temperature, and then backfill with helium. After filling with helium to normal pressure, remove the sample tube and immediately cover it with a rubber stopper, weigh it, and record the weight of the helium-filled sample tube, stopper, and filling rod, which is the gross weight of the sample tube. Use the same sample tube, stopper, and filling rod to perform the following work. The sample weight is obtained by the reduction method.

[0114] 4) Load the weighed sample tube into the analysis station. Add liquid nitrogen to the Dewar flask and enter the sample mass into the analysis file. Set the test parameters and start the adsorption and desorption test process.

[0115] 5) After the test, take out the sample from the sample tube, wash the sample tube and dry it for later use.

[0116] 2. Oxygen content test

[0117] 1) Place the graphene powder in an oven and dry it for 12 hours to completely dry it.

[0118] 2) Turn on the organic element analyzer (EA test), select O mode test, place the dried graphene powder sample in the reactor, weigh the original mass of the sample, crack it at 1150 degrees Celsius in a H2 / He mixed gas atmosphere, and then pass the gas produced by the reaction through carbon powder to convert all the oxygen elements in it into CO gas, and then pass it through the heat island detection to measure the CO content, and then finally get the oxygen content in the sample based on the original mass of the sample.

[0119] 3. Solid content test (weight loss method)

[0120] 1) Place a drying dish at 120℃ with constant weight, lay copper foil flat inside, weigh and record the weight of the dish and copper foil m1.

[0121] 2) Weigh about 5 g of the slurry sample, place it in a watch glass, and record the total mass of the watch glass and the slurry as m2.

[0122] 3) Place the sample in an oven at 120°C, bake for 4 hours, take it out and place it in a desiccator, cool it to room temperature, weigh m3, and calculate the solid content = (m3-m1)*100% / (m2-m1).

[0123] 4. Sheet diameter & thickness test

[0124] 1) 0.1 g of graphene conductive slurry was added into 100 ml of alcohol to prepare a dilute solution, and ultrasonically dispersed for 5 minutes to obtain a diluted graphene conductive slurry.

[0125] 2) Drop the diluted solution on the SEM sample stage, dry it in an oven, place it under the SEM for observation, and measure the size of the graphene sheet structure in the field of view. The average size of 30 samples is taken as the diameter of the graphene sheet.

[0126] 3) Drop the diluted graphene on the AFM sample stage, dry it in an oven, place it under AFM for observation, measure the thickness of the graphene sheet, take the average size of 30 samples as the thickness of the graphene, and then use the average thickness of 0.35nm to convert it to obtain the thickness of the graphene.

[0127] 5. Pole piece test:

[0128] 1. Roller compression test

[0129] 1) Take the rolled pole piece and place it with a 1535mm 2 The circular sampler is used to select 30 small disc samples, and the average surface density of the dressing after removing the foil from the small discs is calculated as M1.

[0130] 2) The average thickness of 10 rolled pole pieces is measured with a micrometer as D, and the average thickness of 10 plain foils is d. The compaction density of the rolled pole piece is calculated as M1 / (Dd).

[0131] 2. Pole piece aperture test (mercury pressure method)

[0132] 1) Add 2 to 3 g of electrode sample into the sample container, place it in the mercury intrusion instrument, and ensure that the container is in good contact with the mercury intrusion instrument.

[0133] 2) Using a pump or instrument, gradually add mercury to the sample container.

[0134] 3) When the sample container is filled with mercury, start recording the flow of mercury.

[0135] 4) Slowly increase the pressure until the mercury completely enters the sample and stops flowing.

[0136] 5) Record the final pressure and volume and perform calculations.

[0137] 3. Liquid absorption test of electrode

[0138] 1) Take a number of positive electrode plates, ensure that there is no pollution or obvious defects on the surface of the plates, and place the plates in an oven at 120°C for 2 hours to remove moisture from the plates.

[0139] 2) Use an electronic balance to weigh the original weight of the electrode as W1.

[0140] 3) Use a pipette or syringe to take a certain amount of electrolyte and slowly drip it on the positive electrode, ensuring that the droplets are evenly distributed on the surface of the electrode. The contact area between the two is S.

[0141] 4) After standing for 3 minutes, wipe the surface of the electrode to remove the absorbed electrolyte and weigh the electrode to obtain a weight W2.

[0142] 5) The amount of liquid absorbed is calculated according to W2-W1 and the area S of the contact with the positive electrode: Liquid absorbed = (W2-W1) / S.

[0143] Battery cell testing:

[0144] Normal temperature 4C / 1C cycle test:

[0145] At 25°C, charge to 4.25V at 4C, let stand for 30 minutes, and discharge to 2.0V at 1C to obtain the initial discharge capacity C0. After standing for 5 minutes, charge to 4.25V at 4C, let stand for 30 minutes, and discharge to 2.0V at 1C to obtain the discharge capacity of the first cycle C1. After 500 cycles, the discharge capacity at this time is measured as C500, and the capacity retention rate under 500 cycles is calculated = C 500 / C0.

[0146] The test results are shown in Table 1 below.

[0147]

[0148] It can be seen from Table 1 that the pole piece of the comparative example without the solid electrolyte-graphene composite material has a larger average pore size, all greater than 53nm, while the average space of the pole piece using the solid electrolyte-graphene composite material is less than 48nm. Therefore, it can be explained that the solid electrolyte-graphene composite material can improve the pore structure of the pole piece. After changing the pore structure, the smaller the pore, the stronger the capillary force of the electrolyte, thereby increasing the liquid absorption of the pole piece. It can also be seen from Table 1 that the average pore size of the embodiment is smaller than that of the comparative example, and the liquid absorption is greater than that of the comparative example. After increasing the liquid absorption, the ion transfer rate in the battery cell can be increased, thereby improving the rate and cycle performance of the battery cell.

[0149] On the other hand, the liquid absorption of Example 3-10 increases compared with that of Example 1-2 because the graphene prepared by chemical method has higher oxygen content and larger specific surface area, which can increase its affinity with the electrolyte. At the same time, the roughness coated on the surface of the main material particles reduces the obstruction of the electrolyte infiltration process and improves the wetting effect of the electrolyte in the positive electrode plate.

[0150] In addition, the oxygen-containing functional groups in the graphene form hydrogen bonds and van der Waals forces with the solid electrolyte carrying oxygen elements, which helps to disperse the solid electrolyte and inhibit its aggregation. Therefore, compared with Examples 1-2, Examples 3-10 have a higher oxygen content and a smaller pore size of the electrode.

[0151] Figure 2 Schematic diagram of SEM characterization of graphene powder prepared by physical and chemical methods. Figure 2 In the figure, the left side is the SEM of the graphene powder of Example 1, and the right side is the SEM of the graphene powder of Example 3. By comparing the SEMs of the two, it can be determined that the graphene powder (i.e., graphene conductive agent) prepared by a chemical method in Example 3 has fewer layers and smaller pores, which further supports the layer number data in Table 1 above. After reducing the number of layers, the liquid absorption of the electrode can be increased.

[0152] Figure 3 This is a schematic diagram of the SEM characterization of graphene-solid electrolyte composite materials prepared by physical and chemical methods and applied to positive electrode sheets. Figure 3 In the figure, the left side is the SEM of the positive electrode sheet of Example 1, and the right side is the SEM of the positive electrode sheet of Example 3. By comparison, it can be seen that the positive electrode sheet prepared by chemical method in Example 3 is thinner and has a smaller interlayer spacing, which increases the wettability of the electrode to the electrolyte, thereby increasing its liquid absorption, thereby improving the ion transmission efficiency and increasing the battery rate.

[0153] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A positive electrode additive, characterized in that: include: A solid electrolyte-graphene composite material is obtained by calcining a raw material mixture including a solid electrolyte and a graphene conductive agent.

2. The positive electrode additive according to claim 1, characterized in that The raw material mixture further comprises carbon nanotubes and / or conductive carbon black.

3. The positive electrode additive according to claim 1 or 2, characterized in that: The mass ratio of the solid electrolyte to the graphene in the solid electrolyte-graphene composite material is 1:1 to 1:

5.

4. The positive electrode additive according to claim 1 or 2, characterized in that: The solid electrolyte-graphene composite material 50 The particle size is 0.5μm~3μm.

5. The positive electrode additive according to claim 1 or 2, characterized in that: The solid electrolyte-graphene composite material contains 0.1% to 2.0% oxygen by mass.

6. The positive electrode additive according to claim 1 or 2, characterized in that: The solid electrolyte is an inorganic solid electrolyte, and the solid electrolyte is selected from at least one of lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), lithium lanthanum zirconium oxide (LLZO), and lithium lanthanum titanium oxide (LLTO); Or, the solid electrolyte is an organic solid electrolyte, and the organic solid electrolyte is selected from at least one of polyethylene oxide (PEO), polyacrylonitrile (PAN), polyamide (PA), and polyurethane (PU); Alternatively, the solid electrolyte is an organic-inorganic composite solid electrolyte, and the organic-inorganic composite solid electrolyte is selected from at least one of a PEO-LATP composite material, a PAN-LLZO composite material, a composite material of polyurethane and LLTO, and a composite material of polyethylene oxide and ceramic material.

7. The positive electrode additive according to claim 1 or 2, characterized in that: The specific surface area of ​​the graphene conductive agent is 258m 2 / g~893m 2 / g.

8. The positive electrode additive according to claim 1 or 2, characterized in that: The solid electrolyte D 50 The particle size is 0.2μm~0.6μm.

9. A method for preparing a cathode additive according to any one of claims 1 to 8, characterized in that: The method comprises: The graphene conductive agent and the solid electrolyte are calcined to obtain a solid electrolyte-graphene composite material as the positive electrode additive.

10. The method according to claim 9, characterized in that If the solid electrolyte is an inorganic solid electrolyte, the calcination temperature is 700° C. to 900° C., the calcination time is 8 to 12 hours, and the atmosphere is an inert gas.

11. The method according to claim 10, characterized in that The method further comprises: Prepare graphene conductive agent by liquid phase exfoliation method or redox method; The liquid phase exfoliation method comprises the following steps: mechanical exfoliation of the expanded graphite raw material in an aqueous phase system for a treatment time of 2 hours to 4 hours, followed by flash drying for 1 hour to 2 hours; The steps of the oxidation-reduction method include: using graphite, concentrated sulfuric acid and potassium permanganate as raw materials, preparing graphite into graphene oxide by an oxidation method, and then obtaining graphene by thermal reduction of the graphene oxide; wherein the thermal reduction temperature is set to 700° C. to 1200° C., the time is 3 h to 8 h, and the atmosphere is an inert gas.

12. A positive electrode sheet, characterized in that: include: A positive electrode current collector, and a positive electrode coating located on one side surface of the positive electrode current collector, wherein the positive electrode coating comprises an active layer and a conductive layer; The active layer comprises a main material, the positive electrode additive according to any one of claims 1 to 8, and a binder.

13. The positive electrode sheet according to claim 12, characterized in that: The additive accounts for 1% to 2% by mass in the positive electrode plate.

14. A battery, characterized in that: Including the positive electrode sheet as described in claim 12 or 13.

15. An electronic device, characterized in that: Comprising the battery of claim 14.

Citation Information

Cited By

  • Solid-state battery, preparation method thereof and power utilization device

    CN121238027A